2013
DOI: 10.1371/journal.pone.0061247
|View full text |Cite
|
Sign up to set email alerts
|

Gene Silencing of BnTT10 Family Genes Causes Retarded Pigmentation and Lignin Reduction in the Seed Coat of Brassica napus

Abstract: Yellow-seed (i.e., yellow seed coat) is one of the most important agronomic traits of Brassica plants, which is correlated with seed oil and meal qualities. Previous studies on the Brassicaceae, including Arabidopsis and Brassica species, proposed that the seed-color trait is correlative to flavonoid and lignin biosynthesis, at the molecular level. In Arabidopsis thaliana, the oxidative polymerization of flavonoid and biosynthesis of lignin has been demonstrated to be catalyzed by laccase 15, a functional enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 38 publications
1
53
0
1
Order By: Relevance
“…In Arabidopsis thaliana , the flavonoid biosynthesis pathway has been characterized mainly using different tt mutants, which have transparent and colorless testa (seed coats) (Holton and Cornish, 1995; Devic et al, 1999; Wan et al, 2002; Xie et al, 2003; Baudry et al, 2006; Lepiniec et al, 2006; Routaboul et al, 2006; Cheng, 2013; Saito et al, 2013). The present study showed that TT10 and AHA10 were involved in seed color formation of rapeseed, but these genes have yet to be successfully used in rapeseed breeding programs (Fu et al, 2007; Stein et al, 2013; Zhang et al, 2013). The flavonoid biosynthesis pathways of Brassica species are much more complex than those of A. thaliana (Supplementary Figure S3); in addition to consisting of more synthesis-related genes, this pathway is also involved in multi-loci interactions, which have been shown to be involved in the formation of seed coat color in B .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In Arabidopsis thaliana , the flavonoid biosynthesis pathway has been characterized mainly using different tt mutants, which have transparent and colorless testa (seed coats) (Holton and Cornish, 1995; Devic et al, 1999; Wan et al, 2002; Xie et al, 2003; Baudry et al, 2006; Lepiniec et al, 2006; Routaboul et al, 2006; Cheng, 2013; Saito et al, 2013). The present study showed that TT10 and AHA10 were involved in seed color formation of rapeseed, but these genes have yet to be successfully used in rapeseed breeding programs (Fu et al, 2007; Stein et al, 2013; Zhang et al, 2013). The flavonoid biosynthesis pathways of Brassica species are much more complex than those of A. thaliana (Supplementary Figure S3); in addition to consisting of more synthesis-related genes, this pathway is also involved in multi-loci interactions, which have been shown to be involved in the formation of seed coat color in B .…”
Section: Discussionmentioning
confidence: 78%
“…In addition, TT2 (R2R3-MYB), TT8 (bHLH), and TTG1 (WDR) modulate proteins, including DFR, LDOX, BAN, and TT12, thereby affecting PA production, and form a complex called MBW (MYB-bHLH-WD40) in the flavonoid pathway (Baudry et al, 2004, 2006; Lepiniec et al, 2006). Previous studies have proposed TTG1, TT8, TT10, TT12 , and AHA10 as candidate genes involved in seed coat color formation in Brassica species (Xie et al, 2003; Fu et al, 2007; Chai et al, 2009; Li et al, 2012; Stein et al, 2013; Zhang et al, 2013; Padmaja et al, 2014). Therefore, we predict that the candidate genes bZIP25, MYC1 , and MYB51 are involved in the flavonoid biosynthesis pathway through different regulator networks in rapeseed (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clades I and II gathered 14 and three B. distachyon laccases, respectively, and some Arabidopsis proteins of unknown functions. Clade III comprised three B. distachyon laccases with AtLAC15 and BnTT10 laccase proteins involved in proanthocyanidin polymerization (Pourcel et al, 2005;Zhang et al, 2013). This result suggests that other members of clade III might also catalyze the oxidation of flavonoids.…”
Section: Bdlac5 and Bdlac6 Proteins Are Closely Related To Lignin-spementioning
confidence: 91%
“…1). In addition, we incorporated in this tree some other laccases reported to catalyze the oxidative polymerization of various phenolics, such as SofLAC from sugarcane (Cesarino et al, 2013), ZmLAC3 from maize (Zea mays; Caparrós-Ruiz et al, 2006), PtLAC3 from Populus trichocarpa (Ranocha et al, 2002), GaLAC1 from Gossypium arboretum (Wang et al, 2008), and Brassica napus Transparent Testa10 (BnTT10; Zhang et al, 2013;Supplemental Table S2). The resulting phylogeny comprised four large clades (Fig.…”
Section: Bdlac5 and Bdlac6 Proteins Are Closely Related To Lignin-spementioning
confidence: 99%